Solar car drive controller and electrical system design - Choi Kian Keong (Universiti Malaysia Perlis, 2008)
Solar car is one of most electric vehicles in humans live today. This project is consists of embedded system design to drive controller and electrical system for solar car prototype. Objectives of this project is study and identify several of drive controller and electrical system of solar car, apply theoretical analysis method to identify critical factors in this prototype solar car drive controller and electrical system design and propose improvements that aim for higher efficiency drive controller and electrical system design. The heart of the drive system is the DC motor controller. The controller is capable and is equipped for full four quadrant operation; i.e. forward/reverse, steering left/right modes. These modes are controller by the logic card contained within the microcontroller. The simulation of this drive controller system design is shown all Pulse Width Modulation (PWM) form and DC motor animation of different speed control switches. The different PWM wave forms is provided different average voltage and current supply to DC motor and the speed of DC motor can observed on DC motor animation. Also the simulation of this drive controller is shown the animation of DC Servo motor steered direction each time the related switch is pressed. From all data collected and analyzed of simulation, this solar car drive controller system and electrical system design is proved that work properly to requirement of this solar car prototype and project objectives.